Stolen Generation: as an example of British and Australian attitudes towards Australian aborigines in the first half of 20th century - Puková, Marie (Univerzita Pardubice, 2011)
The topic of this bachelor thesis is the "Stolen Generation" of Aboriginal children from 1814 to 1969 and the cultural analysis of the forces that shaped this episode of Australian history. The main object is to show how changes in the morals and the values of European culture in the 19th and early 20th century were reflected in the attitudes of British and later Australian settlers towards the native Aboriginal population. Further attention will be paid to more recent changes in the relationship between to ethnic groups. There will also be some consideration of the literary response of the Aboriginal community towards the topic of the "Stolen Generation".
Ukradená Generace jako příklad britských a australských postojů k praobyvatelům Austrálie v první polovině dvacátého století
Keywords: analýza kultury; postoj britských osadniků; osudný dopad; domorodci; moderní australská odezva; ukradená generace; culture analysis; attitude of British settlers; Fatal Impact; Aborigines; modern Australia response; Stolen Generation